Influence of Social Media Marketing Activity Instagram Towards Purchase Intention in Le Bliss Bouquet Cirebon - Selsabilla Al Hakim; Dinda Amanda Zuliestiana (Quantitative Economics and Management Studies, 2022)
Technology today has an important role in various aspects of life. Technology can make it easier for people to carry out daily activities without any limitations. One of the uses of this technology is the implementation of marketing activities that can be carried out through social media. This study aims to determine whether the influence of social media marketing activity carried out by Le Bliss Bouquet has an influence on brand equity, distribution of e-WOM on social media, and purchase intention. Some of the theories used include the theory of social media marketing activity, brand equity, E-WOM, and consumer behavior that can form interest in making purchases. The type of research conducted is causal. Respondent data was collected by distributing questionnaires through social media and the analytical technique used was Structural Equation Modeling (SEM) with the help of SmartPLS software. The sample used in this study were Instagram social media users who had accessed the Le Bliss Bouquet Cirebon Instagram social media account. The results show that the structural equation modeling supports the hypothesis contained in the study and shows a positive influence between social media marketing activity on purchase intention. In addition, brand equity is also considered to have a positive impact on e-WOM and e-WOM maintains a positive influence on purchase intention. It is hoped that the results of this study can be used as an evaluation of the implementation of social media marketing activities carried out by the company because it is considered capable of forming product brand equity and influencing purchase intention